Power and ideas: the legitimisation of the end of the Irish social partnership model during the Eurozone crisis. Issue 1 (2nd January 2022) - Gago, Angie
ABSTRACT: One of the consequences of the Eurozone crisis was the collapse of social concertation. Some authors have explained that the need for fiscal retrenchment deprived governments of resources to offer concessions to trade unions (Regan, 2013). Although these explanations partly explain why social partnership ended, we do not yet know how political actors achieved this institutional change, neither which ideas they used to legitimate it. This article adopts a discursive institutionalist framework (Schmidt, 2008, 2010) to identify the ideas and the causal mechanisms through which political leaders were able to exercise ideational power in a paradigmatic case study: Ireland. The article argues that external constraints during the crisis empowered specific political actors that used the crisis as a 'moment of political opportunity' (Béland, 2005, p. 10) to end the social partnership model. They constructed a communicative discourse to legitimise this change based on the ideas that social partnership was dysfunctional and undemocratic.